2006
DOI: 10.1002/ijc.22216
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment serum endostatin as a prognostic indicator in metastatic gastric carcinoma

Abstract: Endostatin is the C-terminal antiangiogenic fragment of the extracellular matrix protein collagen XVIII, and is generated by tumorderived proteases. The presence of serum endostatin in patients with gastric cancer has not been reported. The authors assessed the serum levels of endostatin in patients with gastric carcinoma and evaluated their association with the levels of vascular endothelial growth factor (VEGF) and the clinical outcome. A total of 107 patients with gastric cancer were included in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Based on the results, the investigators suggested a significant correlation between collagen XVIII expression in tumor tissue and elevated serum endostatin levels [14]. Previously, we showed that higher levels of serum endostatin are linked with poorer prognosis in metastatic gastric carcinoma [18]. In this study, we examined whether collagen XVIII expression is associated with the serum endostatin level in gastric cancer (data not shown).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Based on the results, the investigators suggested a significant correlation between collagen XVIII expression in tumor tissue and elevated serum endostatin levels [14]. Previously, we showed that higher levels of serum endostatin are linked with poorer prognosis in metastatic gastric carcinoma [18]. In this study, we examined whether collagen XVIII expression is associated with the serum endostatin level in gastric cancer (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…However, the role of collagen XVIII in tumor progression and prognosis of hepatocellular carcinoma remains a controversial [13,20]. Previously, we reported an association of elevated pretreatment serum endostatin levels in metastatic gastric carcinoma with poor survival and rapid tumor progression [18]. To our knowledge, the clinical significance of collagen XVIII expression in gastric cancer has not been investigated.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, Woo et al [26] concluded that pretherapeutic serum endostatin (P<0.001) and VEGF (P<0.001) levels were higher in patients with GC. The serum endostatin (P<0.001) and VEGF (P=0.001) levels were significantly higher in patients with metastasis than in patients without distant metastasis.…”
Section: Ang/endostatin Familymentioning
confidence: 99%
“…Despite the acknowledged antiangiogenic functions of endostatin, higher serum endostatin levels are associated with poor differentiation and advanced stage in CRC, gastric cancer and bladder cancer (Li et al, 2012;Szarvas et al, 2012) and with poor prognosis of the patient in bladder cancer, non-small cell lung cancer, gastric cancer and soft tissue sarcoma (Feldman et al, 2001;Suzuki et al, 2002;Woo et al, 2006;Szarvas et al, 2012). The effect of endostatin on endothelial cells depends on the length of exposure (Li et al, 2005), the type of endothelial cells (Schmidt et al, 2004) and the type of growth factor inducing endothelial cell proliferation (Delaney et al, 2006).…”
mentioning
confidence: 99%